2022
DOI: 10.1186/s12931-022-01951-9
|View full text |Cite
|
Sign up to set email alerts
|

The value of ROX index in predicting the outcome of high flow nasal cannula: a systematic review and meta-analysis

Abstract: Background High flow nasal cannula (HFNC) therapy is widely employed in acute hypoxemic respiratory failure (AHRF) patients. However, the techniques for predicting HFNC outcome remain scarce. Methods PubMed, EMBASE, and Cochrane Library were searched until April 20, 2021. We included the studies that evaluated the potential predictive value of ROX (respiratory rate-oxygenation) index for HFNC outcome. This meta-analysis determined sensitivity, spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 24 publications
(71 reference statements)
2
27
0
1
Order By: Relevance
“…The index has also been used to predict HFNC failure in patients with COVID-19 pneumonia [ 13 , 14 ]. Because measurement of the ROX index is feasible, effective, and reproducible, it is widely used to predict HFNC failure [ 15 , 16 ]. To the best of our knowledge, the value of the prediction of NIV failure obtained using the ROX index is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The index has also been used to predict HFNC failure in patients with COVID-19 pneumonia [ 13 , 14 ]. Because measurement of the ROX index is feasible, effective, and reproducible, it is widely used to predict HFNC failure [ 15 , 16 ]. To the best of our knowledge, the value of the prediction of NIV failure obtained using the ROX index is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% of symptomatic COVID-19 cases develop severe disease requiring oxygen support [16]. Simple bedside markers of respiratory compromise in COVID-19 can predict critical care needs and mortality [17][18][19]. Those hospitalised with severe COVID-19 often have a prolonged length of stay (LOS) and may require long periods of mechanical ventilation; thus, they are at high risk for developing ICU-AW [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The ROX index has been closely used in conjunction with the HFNC, serving as a guiding parameter to help monitor this therapy’s success or failure. Since the start of the COVID-19 pandemic, there has been a number of studies corroborating the ROX index as a valuable predictor of the success or failure of the HFNC therapy among COVID-19 patients [ 18 ], as well as non–COVID-19 patients [ 19 ]. Its predictive validity in detecting respiratory-related adverse events has surpassed other instruments, such as the National Early Warning Score, in COVID-19 patients [ 20 ], partly due to the use of FiO 2 as a continuous variable.…”
Section: Introductionmentioning
confidence: 99%
“…Although an ideal cut-off value for therapy success has not been reached, systematic reviews have provided a narrower range of values with adequate predictive capacity for successful HFNC weaning. Junhai et al [ 19 ] have found acceptable specificity (0.72 (95% CI 0.65–0.78)) but low sensitivity (0.67 (95% CI 0.57–0.76)). In a subgroup analysis of COVID-19 patients only, the predictive value was moderate (pooled sensitivity and specificity of 0.71 (95% CI 0.56–0.82) and 0.73 (95% CI 0.63–0.81), respectively), and a cut-off value of > 5 in predicting HFNC failure was reported (sensitivity and specificity 0.59 (95% CI 0.54–0.65) and 0.83 (95% CI 0.79–0.86), respectively).…”
Section: Introductionmentioning
confidence: 99%